Safety and Immunogenicity Analysis of a Newcastle Disease Virus (NDV-HXP-S) Expressing the Spike Protein of SARS-CoV-2 in Sprague Dawley Rats - Tcheou, Johnstone; Raskin, Ariel; Singh, Gagandeep; Kawabata, Hisaaki; Bielak, Dominika; Sun, Weina; González-Domínguez, Irene; Sather, D Noah; García-Sastre, Adolfo; Palese, Peter; Krammer, Florian; Carreño, Juan Manuel (Frontiers in Immunology, 2021)
Despite global vaccination efforts, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve and spread globally. Relatively high vaccination rates have been achieved in most regions of the United States and several countries worldwide. However, access to vaccines in low- and mid-income countries (LMICs) is still suboptimal. Second generation vaccines that are universally affordable and induce systemic and mucosal immunity are needed. Here we performed an extended safety and immunogenicity analysis of a second-generation SARS-CoV-2 vaccine consisting of a live Newcastle disease virus vector expressing a pre-fusion stabilized version of the spike protein (NDV-HXP-S) administered intranasally (IN), intramuscularly (IM), or IN followed by IM in Sprague Dawley rats. Local reactogenicity, systemic toxicity, and post-mortem histopathology were assessed after the vaccine administration, with no indication of severe local or systemic reactions. Immunogenicity studies showed that the three vaccination regimens tested elicited high antibody titers against the wild type SARS-CoV-2 spike protein and the NDV vector. Moreover, high antibody titers were induced against the spike of B.1.1.7 (alpha), B.1.351 (beta) and B.1.617.2 (delta) variants of concern (VOCs). Importantly, robust levels of serum antibodies with neutralizing activity against the authentic SARS-CoV-2 USA‐WA1/2020 isolate were detected after the boost. Overall, our study expands the pre-clinical safety and immunogenicity characterization of NDV-HXP-S and reinforces previous findings in other animal models about its high immunogenicity. Clinical testing of this vaccination approach is ongoing in different countries including Thailand, Vietnam, Brazil and Mexico.